2004
DOI: 10.1108/02651330410539620
|View full text |Cite
|
Sign up to set email alerts
|

China's entry to WTO: global marketing issues, impact, and implications for China

Abstract: The transition from a command economy to a market-based economy has been remarkably successful in China. After 15 years of negotiations, China finally joined the World Trade Organization (WTO) in December 2001. Because of trade and investment liberalization under the WTO, there will be greater competition between Chinese and foreign firms, both inside China and outside China. While there is a great deal of economic literature on China's entry to the WTO, there has been no research on the global marketing impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Tourism was a highlight of economic reform and its development has made significant contribution to the national economy. The large number of publications could also be due to the entry of China into the World Trade Organization (WTO) in 2001, which resulted in decisive influence on tourism development and booming research (e.g., Agarwal and Wu, 2004;Wen, 2001;Wang, 1997).…”
Section: Overview Of Articles Published On China Tourism and Hospitalitymentioning
confidence: 99%
“…Tourism was a highlight of economic reform and its development has made significant contribution to the national economy. The large number of publications could also be due to the entry of China into the World Trade Organization (WTO) in 2001, which resulted in decisive influence on tourism development and booming research (e.g., Agarwal and Wu, 2004;Wen, 2001;Wang, 1997).…”
Section: Overview Of Articles Published On China Tourism and Hospitalitymentioning
confidence: 99%
“…Like Jean-Marc F. Blanchard's article on China's WTO accession in this special issue, it chronicles the 15-year course of China's accession, specifies China's WTO terms, reviews the factors that slowed, stalled and accelerated China's entry at various points along the way, expounds on the economic and social costs that China faced as a consequence of joining the WTO, and details why China accepted the WTO terms it did (Fewsmith, 2001;Lai, 2001;Kim, 2002;Liang, 2002;Breslin, 2003;Feng, 2006). In addition, it delves into the opportunities created for businesses and the obstacles faced by companies seeking to exploit the policy changes China would be making (Mok, 2002;Agarwal and Wu, 2004;Chang et al, 2005). Furthermore, it speculates on the likelihood that China will fulfil its commitments (Chan, 2004;Liew, 2005;Mertha and Zeng, 2005).…”
Section: The Literaturementioning
confidence: 97%
“…The gradual change in shopping habits and consumption needs of the population in these countries along with further economic liberalization allowed many small stores to increase their scale of operation and turn into mini-supermarkets, thus introducing the concept of self-service (Lo & Lin, 2001;Ho, 2005;Lorentz, Wond, & Hilmola, 2007;Marinov, 2005;Shultz, Burbink, Grbac, & Renko, 2005). International supermarket, hypermarket, and discount retail chains such as Carrefour, Metro Cash and Carry, and Wal-Mart were in fact able to penetrate transitional economies only when relatively favorable government regulations related to foreign investment were implemented and when some retail and wholesale modernization effort was already taking place in the respective countries (Lo & Lin, 2001;Ho, 2005;Goldman, 2000;Agarwal & Wu, 2004;Goldman, Ramaswami, & Krider, 2002). However, even at this point, many international firms found that a complete transfer of a particular retail format was not possible owing to local needs and shopping preferences, strict regulations on land usage and lease requirements, and underdeveloped physical infrastructure (Halepete, Iyer, & Park, 2008;Srivastava, 2008;Zinkhan, Fontenelle, & Balazs, 1999;Callichio, Francis, & Ramsay, 2007;Ho & Tang, 2006).…”
Section: Distributive Institution Rigiditymentioning
confidence: 98%